Chad : 2016 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that macroeconomic outcomes in Chad continue to underperform, owing to the major impact of two exogenous shocks: lower oil prices and higher regional insecurity. Oil revenues have collapsed to a fraction of their previous level and are expected to recover only partially and gradually. Economic activity slowed sharply in 2015, with GDP growth estimated to have decelerated to 1.8 percent from 6.9 percent in 2014. The short- and medium-term outlooks remain challenging. Including a contraction of 1.1 percent in 2016, GDP growth is projected to average about 2 percent a year during 2016-18, compared with almost 5 percent during 2013-15.